Optimizing Training Strategies: Enhancing Effectiveness and Performance Outcomes - Purnama, Chamdan (STKIP PGRI SITUBONDO, 2024)
Growing companies tend to shift the paradigm from viewing employees as work tools towards valuing them as competent human resources. Currently, trends show that employees who have new knowledge that is appropriate to the dynamics of changes occurring in the work environment are becoming increasingly important. A focus on human capital, which includes knowledge, education, training and skills, is now more crucial than ever. This research aims to explore whether education and training have an impact on employee performance. The sample in this study consisted of 75 employees selected using a saturated sampling technique. Data analysis was carried out using multiple linear regression with the help of SPSS version 25 software. The research results show that there is a significant positive relationship between education and employee performance, which means that the higher a person's level of education, the higher their performance. In addition, training also has a significant positive effect on employee performance, indicating that a higher level of training will improve the employee's performance